Feasibility study of a health coaching intervention to improve contraceptive continuation in adolescent and young adult women in Philadelphia, Pennsylvania. Issue 3 (24th March 2022) - Akers, Aletha Y.; Skolnik, Ava; DiFiore, Gabrielle; Harding, Jennifer; Timko, C. Alix
Abstract: Introduction: Few interventions to improve contraceptive continuation are tailored to meet the developmental needs of young women under age 25 years. The Health Coaching for Contraceptive Continuation (HC3) intervention was designed to address this gap. In this special report, we describe the rationale for using health coaching, conceptual framework, intervention processes, and findings from a single‐arm feasibility study of the intervention protocol. Methodology: Health coaching is a person‐centered behavioral change approach organized around five main strategies: providing education relevant to health goals, building health self‐management skills, offering patient‐centered counseling, identifying barriers to adherence, and fostering personal accountability for achieving health goals. We used these strategies to affect theory‐driven mediators delineated in the Integrative Model of Behavioral Prediction (intentions, knowledge, attitudes, perceived social norms, and self‐efficacy) and clinical mediators posited to change through program participation (shared contraceptive decision‐making, method satisfaction, quality of life, distress tolerance, experiential avoidance, patient‐coach alliance, and expectations of treatment effect). Experienced sexual health educators completed a manualized, 4‐week health training program adapted from the National Society of Health Coaches. Between March and December 2017, we recruited a convenience sample of sexually‐active women ages 14–21 years who initiated a new contraceptive in the prior 14 days from three urban pediatric clinics in Philadelphia, Pennsylvania. At baseline, participants completed a socio‐demographic questionnaire, contraceptive needs assessment interview, and prioritized reproductive topics to learn more about. We synthesized these data into a coaching plan that guided the monthly coaching sessions which occurred for 6 months following contraceptive initiation. We assessed method adherence and continuation with monthly follow‐up questionnaires and corroborated the findings through electronic medical record and pharmacy refill data review. Exit interviews assessed program acceptability. Feasibility outcomes measured throughout the protocol administration included recruitment and retention success. We used descriptive statistics to assess baseline and follow up questionnaire measures and audio‐recorded and transcribed exit interviews verbatim. Two independent coders used deductive and inductive content analysis coding approaches to identify themes related to program acceptability. Results: Of 92 women approached for the longitudinal intervention, 33 enrolled. Participants' mean age was 17.4 ± 2.1 years. Most were Black ( n  = 24), in high school ( n  = 23), and single/never‐married ( n  = 31). Twenty‐one completed ≥4 coaching sessions. Among the 23 for whom 6‐month contraceptive continuation could be determined, 20 continued their baseline method, 2 switched methods without a gap in use, and 1 discontinued contraceptive use. Five were lost to follow up after enrollment; continuation status was indeterminant for the remaining five. Among the 22 who completed exit interviews, all expressed high program acceptability citing that it provided knowledge‐based benefits, nonknowledge‐based benefits, and an opportunity to develop a positive, supportive relationship with a reproductive health expert. Participants provided feedback on logistical aspects of the program they enjoyed and made suggestions for improvements prior to embarking on a larger efficacy trial. Discussion: Health coaching is a new approach for promoting contraceptive continuation in young women. The conceptual framework, program structure, and feasibility findings demonstrate strong support for the program among participants. Subsequent research must explore program effects on contraceptive continuation and prevention of unintended pregnancy.